Negotiation styles employed by organisational founders in biographical films: The Billionaire (2011) and The Founder (2016) - Razali, Nur Aribah; Che Mat, Nur Huslinda (Universiti Teknologi MARA, 2024)
Negotiation and communication are interdependent, both vital for societal and civilization progress. In cross-cultural business negotiations, entrepreneurs lacking cultural competence can face misunderstandings and miss opportunities for growth and expansion when engaging with individuals from different cultural backgrounds. It is important to rec-ognize that cross- cultural negotiations are distinct from local ones, as overlooking cultural differences can lead to sig-nificant potential problems. Since negotiation studies generally concentrate on politics, there are relatively insufficient studies on negotiations in commerce that reflect organisational founders. Drawing on data from biographical films, this qualitative study aims to identify the negotiation styles of two organisational founders and to compare the styles used by both negotiators originating from distinct cultural backgrounds. Thomas-Kilmann’s Conflict Styles (1974) and Geert Hofstede’s Cultural Dimensions (updated in 2023) were employed as frameworks to facilitate the content analysis of the biographical films The Billionaire (2011) and The Founder (2016). The findings of the study suggest that there is an influence on the way individuals and society perceive the importance of negotiation skills in resolving disputes in daily life and on a global basis. Thus, this study could potentially enrich academia libraries by providing a foundation for future scholarly inquiry.